Equalizing educational opportunities of students with disabilities and special educational needs – new challenges for higher education in Poland - Całek, Grzegorz; Niedbalski, Jakub; Racław, Mariola; Sałkowska, Marta; Sztobryn-Giercuszkiewicz, Joanna; Żuchowska-Skiba, Dorota; Agnieszka Gralak (Disability and education, 2023)
In the article, the author considers the processes of change in higher education in the context of supporting people with special needs, including students with disabilities. The author reflects on the impact of social, legal, and economic transformations on the accessibility of universities and supporting people with disabilities in their academic education. The considerations derive from the author’s experience as a researcher and a person actively participating in shaping the policy of equalizing educational opportunities at universities in Poland. The publication presents threats and chances resulting from new situations, often crisis ones, currently faced by higher education institutions in Poland.